If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -39 = 90 Reorder the terms: -39 + 4x = 90 Solving -39 + 4x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '39' to each side of the equation. -39 + 39 + 4x = 90 + 39 Combine like terms: -39 + 39 = 0 0 + 4x = 90 + 39 4x = 90 + 39 Combine like terms: 90 + 39 = 129 4x = 129 Divide each side by '4'. x = 32.25 Simplifying x = 32.25
| -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 | | 3m+167=55+4m | | 12y+22=9y | | 3x(x+20)=44 | | -11+8x=-67 | | -2p+28=6p-44 | | -6(x+2)-13=10+1 | | (-10x+35)*(5)=x | | 9t=42 | | 9(-8)-4((-8)-7)= | | -2x+7+7x=-3 | | -65+2x=33-5x | | 7c-4c=78+12 | | 34-5x=-21 | | 6y-90=5y-75 | | 5(t-6)+5t=5(2t+2)-9 | | (-10x+35)*(5)= | | (6-2c)+(3c-4)= | | 0.5+0.7=-0.75 |